Novel IncFII plasmid harbouring blaNDM-4 in a carbapenem-resistant Escherichia coli of pig origin, Italy. (24th August 2020) - Diaconu, Elena L; Carfora, Virginia; Alba, Patricia; Di Matteo, Paola; Stravino, Fiorentino; Buccella, Carmela; Dell'Aira, Elena; Onorati, Roberta; Sorbara, Luigi; Battisti, Antonio; Franco, Alessia
Abstract: Objectives: To the best of our knowledge, we describe the first evidence in Europe of an MDR, bla NDM-4 -positive Escherichia coli isolated from a food-producing animal, harboured by a novel IncFII plasmid of which we report the complete sequence. Methods: One bla NDM-4 -positive E. coli isolated in 2019 from the caecal contents of a fattening pig in Italy was in-depth characterized by combined bioinformatic analysis of Oxford Nanopore long reads and Illumina short reads, for in silico typing, determination of the bla NDM-4 genetic context and full reconstruction of the bla NDM-4 –carrying plasmid. Results: The isolate belonged to ST641 and to the genoserotype O108:H23 and tested positive for different virulence genes and plasmid replicons. The MDR phenotype of resistance to all β-lactams, carbapenems, sulfamethoxazole and trimethoprim was mediated by bla TEM-1B, bla NDM-4, sul1 / sul3 and dfrA12, respectively. The bla NDM-4 gene was harboured by a novel 53 043 bp IncFII plasmid (pMOL412_FII) composed of four main genetic regions, including an MDR region (MRR-NDM-4) of 16 kb carrying bla NDM-4 and several antimicrobial resistance genes located in a class 1 integron. pMOL412_FII was closely related to another ∼90.3 kb plasmid (pM109_FII) harbouring bla NDM-4 in an E. coli isolated from a human patient in Myanmar. Conclusions: To the best of our knowledge, we have identified for the first time in Europe an NDM-producing Enterobacterales in livestock and resolved the complete sequence of the novel pMOL412_FII plasmid harbouring bla NDM-4 in an MRR. A global One Health approach, comparing genomic data from different sources and geographical areas, may help to trace back and control possible plasmid-borne carbapenemase gene transmission between animals and humans and along the food chain at international level.